Analisis Etika Komunikasi Film Animasi Syamil Dodo Sebagai Konten Edukasi Islam - Peni Alisani Sopi; Salis Elmadani; Ela Sari; Naila Nadya N; Hisny Fajrussalam (Universitas Majalengka, 2022)
Various digital media can be used as a means of communication, one of which is the production of animated films used to convey educational messages on Islamic topics. During the production process of a film with Islamic content, certain points must be taken into account so that the content can be maintained in accordance with the only applicable rule of communication ethics in Islam. The purpose of this study is to analyze the communication messages included in the animated series